Structural, morphological, enhanced magnetic properties and antibacterial bio-medical activity of rare earth element (REE) cerium (Ce3+) doped CoFe2O4 nanoparticles - Elayakumar, K.; Dinesh, A.; Manikandan, A.; Palanivelu, Murugesan; Kavitha, G.; Prakash, S.; Thilak Kumar, R.; Jaganathan, Saravana Kumar; Baykal, A. (Journal of magnetism and magnetic materials, 2019)
•Rare earth element Ce3+ doped CoFe2O4 NPs were prepared by simple sol-gel combustion technique.•Cerium was successfully substituted into the spinel lattice without any distortion.•Powder XRD and SEM along with EDX studies confirmed the pure phase formation.•There was a substantial decrease in the crystallite size on doping with Ce3+.•Magnetic properties altered by the addition of Ce3+ in the CoFe2O4 matrix. In this present study, we made an attempt for the different concentration of rare earth element (REE) Cerium (Ce3+) doped cobalt ferrite (CoFe2O4) nanoparticles (NPs) were prepared by the simple sol-gel combustion technique. Cerium was successfully substituted into the spinel lattice without any distortion. It was analyzed the effect of Ce3+ ions doping on structural, morphological, magnetic properties and antibacterial activities using the various instrument techniques. Powder XRD and SEM along with EDX studies confirmed the pure phase formation Ce3+ doped CoFe2O4 NPs and spherical shaped agglomerated nanoparticles morphology without any other impurity. The well resolved broad peaks in the XRD pattern clearly indicated the nanosized, single phased, cubic spinal nature of these samples. There was a substantial decrease in the crystallite size on doping with Ce3+. A more in-depth morphological study was facilitated using the TEM and SAED analysis. TEM investigation revealed random shaped, sharp edged nanoparticles with a normally facetted morphology. The presence of distinctive diffractions spots on the SAED pattern indicated the formation of nanoparticles that are highly crystalline in nature. The magnetic response of the Ce3+ doped CoFe2O4 NPs was recorded at room temperature (RT) using the VSM technique. The magnetic properties have been seen to be altered by the addition of Ce3+ in the CoFe2O4 matrix. The decrease in the saturation magnetization (Ms, emu/g) with the increase in Ce3+ content rendered the synthesized sample applicable in field of antenna construction. This change will be also suitable for reducing the size of the antenna. The antibacterial activity of Ce3+ doped CoFe2O4 nanoparticles was found to be enhanced with increase in Ce3+ doping level as it cause a reduction in the grain size.